Meningkatkan Hasil Belajar IPAS Materi Sistem Pencernaan Manusia Siswa Kelas V SDN Banyuajuh 5 melalui Penerapan Media Audio Visual - Akhmad Fauzi Rizal; Lysanul Fasihah; Imam Fahrur Rozy; Nurul Jannah; Moh Ilham Arifin (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2026)
This study aimed to determine the effectiveness of audiovisual learning media in improving fifth-grade students’ learning outcomes on the topic of the human digestive system at SDN Banyuajuh 5. The study was motivated by students’ low learning achievement and difficulties in understanding abstract material, therefore audiovisual media were utilized to create a more engaging, interactive, and understandable learning process. This research employed the Kemmis and McTaggart Classroom Action Research model consisting of two cycles, including planning, action, observation, and reflection stages. The participants of this study were 22 fifth-grade students. Data were collected through interviews, observations, tests, and documentation, and data were analyzed using mixed descriptive analysis, combining quantitative percentages for student mastery and qualitative descriptive analysis for classroom. The findings revealed that the implementation of audiovisual learning media effectively improved students’ learning outcomes, as indicated by the increase in the average scores from 65 in the pre-cycle to 77.27 in cycle I and 89.09 in cycle II. In addition, students’ motivation, participation, and activeness in the learning process also increased significantly. Therefore, audiovisual media can be considered an effective learning tool to enhance students’ understanding and achievement in science learning.